2017
DOI: 10.1111/1462-2920.13826
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of the DNA damage‐inducible network in the Patescibacteria

Abstract: Metagenomics provide unprecedented insights into the genetic diversity of uncultivated bacteria inhabiting natural environments. Recent surveys have uncovered a major radiation of candidate phyla encompassing the Patescibacteria superphylum. Patescibacteria have small genomes and a presumed symbiotic or parasitic lifestyle, but the difficulty in culturing representative members constrains the characterization of behavioural and adaptive traits. Here we combine in silico and in vitro approaches to characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 72 publications
(103 reference statements)
0
26
0
Order By: Relevance
“…Last, the literature also provides an indication that several CPR/ Patescibacteria representatives might have symbiotic lifestyles (Anantharaman et al, 2016;Nelson & Stegen, 2015;Sánchez-Osuna, Barbé, & Erill, 2017). For example, He et al (2015) cultivated the first Saccharimonadia, TM7x, and suggested that this organism lives in an obligate symbiotic association with Actinomyces odontolyticus in the human oral cavity.…”
Section: Ecological Traits Potentially Involved With a Symbiotic LImentioning
confidence: 99%
“…Last, the literature also provides an indication that several CPR/ Patescibacteria representatives might have symbiotic lifestyles (Anantharaman et al, 2016;Nelson & Stegen, 2015;Sánchez-Osuna, Barbé, & Erill, 2017). For example, He et al (2015) cultivated the first Saccharimonadia, TM7x, and suggested that this organism lives in an obligate symbiotic association with Actinomyces odontolyticus in the human oral cavity.…”
Section: Ecological Traits Potentially Involved With a Symbiotic LImentioning
confidence: 99%
“…Patescibacteria are part of the Candidate Phyla Radiation with ultra-small genomes and have a presumed symbiotic or parasitic lifestyle ( Sánchez-Osuna et al, 2017 ; Lemos et al, 2019 ). Members of Patecibacteria were found to be enriched in the disease lesions of coral species from Thailand ( Roder et al, 2014 ) and the Florida Reef Tract ( Meyer et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the four strongest increasing phyla, i.e., Verrucomicrobia, Actinobacteria, Cyanobacteria, and Bacteroidetes, are all considered typical freshwater bacteria ( Newton et al, 2011 ) and have also been found previously in freshwater by Iliev et al (2017) and Kim et al (2018) and others. Patescibacteria were first reported in groundwater and sediments of anoxic environments ( Elshahed et al, 2005 ; Youssef et al, 2011 ; Wrighton et al, 2012 ), but showed to be widespread in most semiaquatic habitats ( Sánchez-Osuna et al, 2017 ). Rokubacteria, also found in groundwater samples, are most closely related to the phylum Nitrospira.…”
Section: Discussionmentioning
confidence: 99%